Konseptualisasi Otonomi Khusus dalam Tinjauan Otonomi Daerah: Konstruksi dan Formulasi - Razak, Askari (Universitas Serang Raya, 2023)
The development of the government system in Indonesia has resulted in significant changes in the form of granting autonomy to the regions. Regional autonomy includes the granting of authority to regions to regulate local issues in accordance with the needs and characteristics of the region. Special autonomy is a variation of the concept of regional autonomy that gives special authority and responsibility to regions with certain characteristics. The purpose of this research is to analyze the way the concept and implementation of special autonomy is interpreted in the situation of regional autonomy. This research uses a normative legal approach method to examine relevant legal regulations and literature related to this topic. The results show that special autonomy is an important step in building governance that is responsive to local needs. While recognizing the privileges of regions with special characteristics, special autonomy must still maintain the unity of the state and respect the values of diversity. The implementation of special autonomy has had a positive impact on regional empowerment, but needs to be improved to remain in line with national goals and human rights. The interaction between the central and local governments in the context of special autonomy also needs to be maintained and strengthened to achieve sustainable and inclusive development throughout Indonesia.